Pedagogical Approaches in The Light of Rumi: From Reflections to Integrations - Abd Rahim, Siti Noor Fauziah (IIUM Journal of Educational Studies, 2016)
A soulful curriculum acknowledges and places an importance to life’s ultimate questions and man’s inner dimension. It pursues a balance and convergence between our inner and outer lives. In Islam, there is no separate discipline of ethics and religion. Islam is founded on the principles of belief and righteous action. In this sense, a meaningful education should not only focus on training the mind to retain and retrieve knowledge per se but to nurture a personality with good characters and behaviours. However, the reality that we are facing today in the education system is the reverse of that. The exclusion of ethical and spiritual dimensions in pedagogical approaches is not only observed in present practices but also in existing references, concepts, and theories in the field of education, philosophy, and psychological literature. Modern theories are inadequate to act as a drive for the transformation of an individual’s personality. Therefore, this paper aimed to explore the pedagogical approaches reflected from a prominent Muslim philosopher and spiritual master, Mawlana Jalal al-Din Rumi (1207-1273 A.D) towards fostering a balanced and excellent personality through education. The main contributions of Al-Rumi that are of great importance for today’s educators are: God-consciousness as the foundation of learning; the need to instill love and compassion through service learning; making learning enjoyable; and emphasis on experiential outdoor learning. Practical pedagogical implications of these were discussed in the light of educational psychology perspectives for educators to integrate these approaches in their teaching and learning activities in the classroom.